Spatiotemporal distribution and influencing factors of Chinese marine protected areas under a social-ecological system framework - Chen, Mingbao; Xu, Zhibin; Wang, Yuhao (Frontiers in Marine Science, 2025)
IntroductionDespite China’s devotion to marine biodiversity by conserving 12.98% of its seas, recent years saw the more flattened growth of marine protected area (MPA) establishment. Understanding the establishment mechanisms of MPAs is crucial for protecting marine wildlife and achieving balanced conservation and development. However, traditional linear or generalized linear models are insufficient to capture complex nonlinear effects between marine ecosystems and society.MethodsAdapting the social-ecological system (SES) framework, from the perspective of public goods decision-making, this paper uses overdispersion-robust Poisson pseudo-maximum likelihood (PPML) regressions with high-dimensional fixed effects to study the distribution pattern and factors influencing MPA establishment in 49 Chinese coastal cities that built MPAs during 1998-2020. It also developed a mathematically based algorithm to locate thresholds where effects change.ResultsResults show GDP over ¥55 billion (1998-based, equal to ¥106.5 billion in 2020) to be conducive to MPA establishment, while built-up areas over 63 km² are antagonistic to MPA development. Illustrated by an N-shaped curve, the article supplements previous studies of the U-shaped environmental Kuznets curve in MPA establishment, providing new theoretical insights from a complex system perspective.DiscussionDrawing on the results, practical implications were given for balance between conservation and development, spatial-ecological and socioeconomic alignment and top-down adaptive governance, with a list of prioritized coastal cities to receive conservation fund as 2030 looms. The conclusions also pertain to global nonlinear MPA development and merit future studies to deepen MPA establishment research with higher-order interactions and complex dynamics.